2009
DOI: 10.1089/end.2008.0546
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cystoscopic Stent Placement in Robot-Assisted Pyeloplasty: A Novel and Efficient Technique

Abstract: This novel technique is a simple and efficient method of stent placement during RAP. It is performed simultaneously without the need for additional procedures, repositioning, or radiation exposure. Application of this technique may result in decreased operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A retrograde approach with flexible cystoscopy and extended surgical field has been reported. Flexible cystoscopy with the patient in the lateral position can be difficult especially in male infants [Wayment et al . 2009].…”
Section: Discussionmentioning
confidence: 99%
“…A retrograde approach with flexible cystoscopy and extended surgical field has been reported. Flexible cystoscopy with the patient in the lateral position can be difficult especially in male infants [Wayment et al . 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues et al used methylene blue to fill the bladder and its appearance through the stent holes as an indication of proper positioning [15], although this is unreliable if concomitant vesicoureteric reflux is present. Others reported the intraoperative placement of the JJ stent using timeconsuming flexible cystoscopy [16]. In order to avoid the second anesthetic for JJ removal, Yucel et al [17] reported the use of a urethral dangler to remove the stent, although this required cystoscopy for placement.…”
Section: Discussionmentioning
confidence: 99%
“…Fiori et al and Wayment et al described the retrograde approach with flexible pneumo-cystoscopy and pointed out its utility [ 32 , 33 ]. Wu et al developed and described a new method in which retrograde and anterograde techniques are used together [ 34 ].…”
Section: Introductionmentioning
confidence: 99%